PENGEMBANGAN E-MODUL BERBANTUAN CANVA GUNA MENINGKATKAN PENALARAN MATEMATIS MATERI PENGURANGAN DAN PENJUMLAHAN PECAHAN SISWA KELAS V GUGUS PRINGGODANI - Wardhani, Sintya Prajna; Andrijati, Noening (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
The purpose of this study is to develop a canva-assisted e-module teaching material as an effort to improve the mathematical reasoning skills of class V students of the Pringgodani Group on addition and subtraction of fractions as well as to analyze the effectiveness and feasibility of canva-assisted e-modules. This research is a development research with the Plomp development model. Data analysis was carried out by normality test, homogeneity test, t-test, and N-Gain test. The results of the study showed that the feasibility assessment of e-modules by material experts was 84.6% on the very feasible criteria, 94.2% on the very feasible criteria, and practitioner experts at 92.5% with very feasible criteria. Based on the results of the t-test and the N-gain test on a limited scale and a wide scale, the e-module was declared effective in improving the mathematical reasoning skills of students in class V of the Pringgodani Group.